Interdependence of Liquidity Problems in the Financial Sector - Sebastian Missio (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
The paper analyses problems arising from the interdependence of liquidity provision in the financial system. Findings document, that liquidity shortage of minor financial players can translate into liquidity shortage for systemic relevant players, thereby putting the proper functioning of the overall financial system on the line. As contractual mechanisms to safeguard against this threat are absent in the wake of market frictions, prudent regulation and governmental provision of external liquidity is asked for in order to solve these problems.
Keywords: G01; G21; 330; Illiquidity; Insolvency; Contagion; Bankenliquidität; Bankenkrise; Ansteckungseffekt; Finanzsektor; Geldpolitik; Regulierung; Theorie